Patient priorities and decision-making process when choosing between colonic investigation alternatives: a qualitative interview study - Shaun Treweek; Philip Wilson; Campbell MacLeod; Angus James Mackintosh Watson; Samantha Robinson (BMJ Open Gastroenterology)
Objective To establish patients’ perceptions of decision-making and prioritisation of test attributes when considering a colonic investigation.Methods National Health Service Highland patients on the waiting list for a colon capsule endoscopy (CCE) and colonoscopy were invited to undergo a semistructured qualitative telephone interview. A diverse sample was sought using a purposive sampling strategy, aiming for differences in age, gender and test awaited between participants. An interview guide was developed using an iterative approach and published data on patients’ experience of colonic investigations. Data were analysed using phenomenological approach and thematic analysis.Results Between 12 June 2022 and 02 August 2022, 12 patients underwent telephone interviews. Nine of those patients were on the waiting list for colonoscopy and three were waiting for a CCE. Patients described a mixed level of involvement in the decision-making process for a colonic investigation; some were not involved in the process at all, while others were guided by their clinician. The most important test aspect reported by patients was diagnostic quality, focused on getting a diagnosis, ruling out cancer or the diagnostic accuracy of the test. The importance of the waiting time for the test, the amount of pain or discomfort experienced during the test and the invasiveness of the test were also discussed by patients.Conclusion Through qualitative interviews, we have identified patients’ priorities for colonic investigations, which should be further explored to quantify the value patients place on these aspects of the test. Areas of improvement in the decision-making process have been reported, which could be addressed to improve patient care.Trial registration number NCT05391529.